The Development of an International Oncofertility Competency Framework: A Model to Increase Oncofertility Implementation. (30th May 2019) - Anazodo, Antoinette; Laws, Paula; Logan, Shanna; Saunders, Carla; Travaglia, Jo; Gerstl, Brigitte; Bradford, Natalie; Cohn, Richard; Birdsall, Mary; Barr, Ronald; Suzuki, Nao; Takae, Seido; et al.
Abstract: Background: Despite international evidence about fertility preservation (FP), several barriers still prevent the implementation of equitable FP practice. Currently, oncofertility competencies do not exist. The aim of this study was to develop an oncofertility competency framework that defines the key components of oncofertility care, develops a model for prioritizing service development, and defines the roles that health care professionals (HCPs) play. Materials and Method: A quantitative modified Delphi methodology was used to conduct two rounds of an electronic survey, querying and synthesizing opinions about statements regarding oncofertility care with HCPs and patient and family advocacy groups (PFAs) from 16 countries (12 high and 4 middle income). Statements included the roles of HCPs and priorities for service development care across ten domains (communication, oncofertility decision aids, age‐appropriate care, referral pathways, documentation, oncofertility training, reproductive survivorship care and fertility‐related psychosocial support, supportive care, and ethical frameworks) that represent 33 different elements of care. Results: The first questionnaire was completed by 457 participants (332 HCPs and 125 PFAs). One hundred and thirty‐eight participants completed the second questionnaire (122 HCPs and 16 PFAs). Consensus was agreed on 108 oncofertility competencies and the roles HCPs should play in oncofertility care. A three‐tier service development model is proposed, with gradual implementation of different components of care. A total of 92.8% of the 108 agreed competencies also had agreement between high and middle income participants. Conclusion: FP guidelines establish best practice but do not consider the skills and requirements to implement these guidelines. The competency framework gives HCPs and services a structure for the training of HCPs and implementation of care, as well as defining a model for prioritizing oncofertility service development. Implications for Practice: Despite international evidence about fertility preservation (FP), several barriers still prevent the implementation of equitable FP practice. The competency framework gives 108 competencies that will allow health care professionals (HCPs) and services a structure for the development of oncofertility care, as well as define the role HCPs play to provide care and support. The framework also proposes a three‐tier oncofertility service development model which prioritizes the development of components of oncofertility care into essential, enhanced, and expert services, giving clear recommendations for service development. The competency framework will enhance the implementation of FP guidelines, improving the equitable access to medical and psychological oncofertility care. Abstract : Despite the available fertility preservation guidelines, barriers still exist that hinder the implementation of oncofertility practice. This article reports an oncofertility framework that defines the key components of oncofertility care, including a model for service development and the role of health care professionals across specialities.